1985
DOI: 10.1139/b85-238
|View full text |Cite
|
Sign up to set email alerts
|

Import and unloading of 14C assimilate into mature leaves of Coleus blumei

Abstract: 1985. Import and unloading of I4C assimilate into mature leaves of Coleus blumei. Can. J. Bot. 63: 1700-1707. Mature leaves of Coleus blumei Benth. were tested for their ability to import I4C assimilate, to unload and metabolize it, and to transfer it to the mesophyll. To enhance the potential for import, plants were preconditioned by removal of shoot tips and axillary branches, by 48 h of darkness, and by removal of roots. One mature leaf on each plant was isolated in a C02-free chamber and kept in the light … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1985
1985
1991
1991

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In dicotyledonous plants, the mesophyll of the sink leaf strongly attracts assimilate only when the leaf is subjected to drastic treatments, such as the application of benzyladenine (Quinlan and Weaver 1969) or perhaps injury. Similarly, recent studies of the Princeton strain of Coleus blumei (Fisher and Eschrich 1985) have shown that significant amounts of imported "C are unloaded and transported to the mesophyll only under conditions of predarkening of the plant, sink limitation, lack of C02 around the sink leaf, and relatively heavy feeding of I4CO2 to all of the source leaves. Even then, not all mature leaves exhibited such transport, and the accumulation of imported ' ' C in the rnesophyll was considerably less than in young developing leaves (Turgeon 1980).…”
Section: Introductionmentioning
confidence: 90%
“…In dicotyledonous plants, the mesophyll of the sink leaf strongly attracts assimilate only when the leaf is subjected to drastic treatments, such as the application of benzyladenine (Quinlan and Weaver 1969) or perhaps injury. Similarly, recent studies of the Princeton strain of Coleus blumei (Fisher and Eschrich 1985) have shown that significant amounts of imported "C are unloaded and transported to the mesophyll only under conditions of predarkening of the plant, sink limitation, lack of C02 around the sink leaf, and relatively heavy feeding of I4CO2 to all of the source leaves. Even then, not all mature leaves exhibited such transport, and the accumulation of imported ' ' C in the rnesophyll was considerably less than in young developing leaves (Turgeon 1980).…”
Section: Introductionmentioning
confidence: 90%
“…Turgeon (1984) has shown that both albino and darkened, normal tobacco leaves cease to import at the same developmental age as do normal light grown tobacco leaves. Several studies have shown that once a leaf has completed the sink-to-source transition, it can be induced to import by subjecting it to darkness, low COz, or surgical manipulation (Blechschmidt-Schneider, 1984;Blechschmidt-Schneider and Eschrich, 1985;Fisher and Eschrich, 1985;Quinlan and Weaver, 1969;Thrower and Thrower, 1980;Weisberg et al, 1988). In only one case (the nonchlorophyllous, or albino, tissue of Coleus blumeD, however, were assimilates transported from the veins to the mesophyll of mature leaves.…”
Section: Introductionmentioning
confidence: 99%
“…To further test the model of assimilate-signal cotransport, we shaded a source leaf for several days to convert the leaf into a sink organ (22,23) and then wounded a different source leaf two nodes above it. Accumulation of win3 transcripts was detected in the shaded leaf (Fig.…”
mentioning
confidence: 99%